Calcium phosphate mineralization controlled by carboxymethyl cellulose-g-polymethacrylic acid. Issue 3 (2nd July 2016) - Salama, Ahmed; Abou-Zeid, Ragab E.; El-Sakhawy, Mohamed
ABSTRACT: Carboxymethyl cellulose-grafted polymethacrylic acid (CMC-g-PMAA) was synthesized by graft copolymerization process onto carboxymethyl cellulose backbone using methacrylic acid as a monomer and ammonium persulfate as a free radical initiator. CMC-g-PMAA was employed as dispersed template for controlling calcium phosphate mineralization from aqueous solutions at different copolymer contents and pHs. Hybrids with different morphologies and particles diameter were investigated by adjusting of preparation conditions. Synthesized hybrids were characterized by FT-IR, SEM, XRD, and particle size analyzer. Such functionalized hybrids with complex morphologies can be manipulated as a novel reinforcing fillers, ceramic precursors, or biomedical implants.